Analysis and comparison of stock market indices design methods: eg US and Egypt market indices - Metwally, Samar Mostafa Mansour (Arab Journal for Sciences and Research Publishing, 2016)
This research aims to study and analyze the most important methods of building and configuring the stock market indices, in addition to present the main stock market indices in the United states and Egypt, to achieve that the researcher has used the Comparative descriptive analytical methodology, to conclude that there are different techniques to calculate the market index’s value, there are mainly three approaches; based on value, price and Relative weights. They also differ according to how they were build. Their advantages, disadvantages and the response to any change or modification differ according to their configuring method.